Referent control of action and perception Challenging conventional theories in behavioral neuroscience - Feldman, Anatol G. (Springer New York : Imprint: Springer, 2015)
This book provides a long-awaited description of a classic motor control theory of action and perception - referent control. Strictly based on experimental material, this theory places action and perception in the context of physical laws to offer solutions of several classical problems in behavioral neuroscience and neurological pathologies. The author re-visits and refines many basic concepts in behavioral neuroscience, including central pattern generators, reflexes, and motor learning. Further, he provides many examples of how task-specific referent control of action and perception can be accomplished by the nervous system. This information may help researchers design theory-driven experiments that address the question of how actions are controlled and how changes in biomechanical characteristics emerge without pre-programming. This book may be interesting to researchers, students in behavioral neurosciences as well as to a broader audience who want to know how action and perception are accomplished by the nervous system.